U.S. banks' exposures to climate transition risks - Hyeyoon Jung; Jo\~ao A. C. Santos; Lee Seltzer (Federal Reserve Bank of New York, 2024)
We find that banks' credit exposures to transition risks are modest. We build on the estimated sectoral effects of climate transition policies from general equilibrium models. Even when we consider the strictest policies or the most adverse scenarios, exposures do not exceed 14 percent of banks' loan portfolios. We also find that commonly used carbon emissions can explain at most 60 percent of bank exposures estimated off general equilibrium models. Moreover, we find evidence of bank management of transition risk exposures. Banks that signed the Net-Zero Alliance have reduced their exposures compared to non-signatories, mainly by cutting lending to the riskiest industries.
Keywords: G21; H23; Q54; 330; banks' climate risk exposures; climate transition risks; NGFS scenarios